Історія українсько-російських бібліологічних зв‘язків у джерелах особового походження (20-ті рр. ХХ ст.) - Ківшар, Т.І.; Новальська, Т.В. (Українська біографістика, 2010)
Published documents and brief overview of correspondence between Yurii Mezhenko, Dmitro Balyka, Illya Vugman and Boris Borovych with Volodymyr Bank, which are stored at the National Russian library manuscript department and related to the development of Soviet system of personnel training in library science, book science and bibliography science fi elds in 20 years of XX c.